1997
DOI: 10.1302/0301-620x.79b1.6814
|View full text |Cite
|
Sign up to set email alerts
|

Sensory And Sympathetic Innervation Of The Vertebral Endplate In Patients With Degenerative Disc Disease

Abstract: We obtained intervertebral discs with cartilage endplates and underlying cancellous bone at operation from patients with degenerative disc disease and then used immunohistochemical techniques to localise the nerves and nerve endings in the specimens. We used antibodies for the ubiquitous neuronal protein gene product 9.5 (PGP 9.5). Immunoreactivity to neuropeptide Y was used to identify autonomic nerves and calcitonin gene-related peptide (CGRP) and substance P to identify sensory nerves. Blood vessels were id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
135
1
16

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(159 citation statements)
references
References 27 publications
4
135
1
16
Order By: Relevance
“…The presence of these reactions in both cohorts is noteworthy because these reactions have been implicated in the development of pain. Specifically, increased vascularization (angiogenesis) and sensory nerve growth are closely linked processes [5,24]; and tissue necrosis or cell death results in the release of proinflammatory cytokines and other factors that initiate persistent pain by directly activating nociceptive sensory neurons [6,38]. Both reactions can lead to maladaptive plasticity and neural disease states, which raises the question whether these tissue responses contributed to neuropathic pain in both fixed-and mobile-bearing L-TDR patients.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of these reactions in both cohorts is noteworthy because these reactions have been implicated in the development of pain. Specifically, increased vascularization (angiogenesis) and sensory nerve growth are closely linked processes [5,24]; and tissue necrosis or cell death results in the release of proinflammatory cytokines and other factors that initiate persistent pain by directly activating nociceptive sensory neurons [6,38]. Both reactions can lead to maladaptive plasticity and neural disease states, which raises the question whether these tissue responses contributed to neuropathic pain in both fixed-and mobile-bearing L-TDR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Discs which cause low back pain have higher concentrations of sensory nerves than are seen in those which do not cause such pain. 14,15 The sensory nerves in the former are found in the endplates and in the nucleus pulposus and lose their normal relationship with blood vessels. The ingrowth of nerves into degenerate discs which cause low back pain may be mediated by chemotactic substances released by the degenerating disc.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown, however, that degenerate discs in these patients contain more nociceptive nerve endings in the endplates of the disc and in the nucleus pulposus than do degenerate discs which do not cause low back pain. 14, 15 We have therefore compared levels of production of the proinflammatory mediators tumour necrosis factor alpha (TNF␣), interleukin-1beta (IL-1␤), interleukin-6 (IL-6), interleukin-8 (IL-8) and prostaglandin E 2 (PGE 2 ), in disc tissue from patients undergoing discectomy for sciatica with those from patients undergoing fusion for discogenic low back pain. …”
mentioning
confidence: 99%
“…Additional studies have identified nerve fibres and blood vessels in the endplates and subchondral bone in degenerate discs suggesting that tissue repair may be associated with back pain [11,17].…”
mentioning
confidence: 99%